Rock art studies : news of the world V - Bahn, Paul G.; Franklin, Natalie R.; Strecker, Matthias; Dėvlet, E. G. (Archaeopress, 2016)
This is the fifth volume in the series. Like the previous volumes, it covers rock art research and management across the globe over a five-year period, in this case the years 2010 to 2014 inclusive.